The Role of Social Media in Shaping Public Discourse among Generation Z: Trends, Challenges, and Implication - Nur Alifah (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2026)
In the digital age, social media has become a pivotal platform for public discourse, particularly among Generation Z. This demographic, known for its digital proficiency, utilizes platforms like Instagram, TikTok, and Twitter to engage in activism, share opinions, and build communities. However, these platforms also present challenges, such as the spread of misinformation, the amplification of polarization, and algorithm-driven content curation. This study aims to analyze the trends, challenges, and implications of social media's role in shaping public discourse among Generation Z. Using a qualitative phenomenological approach, the research collected data through semi-structured interviews and content analysis. Thematic analysis revealed that 35% of social media content is polarizing, often creating ideological echo chambers, while 30% consists of misinformation, undermining trust and informed decision-making. Conversely, activism-related content, accounting for 25% of analyzed posts, highlights the potential for social media to foster civic engagement. The study concludes that while social media empowers Generation Z to participate in societal conversations, it also perpetuates significant challenges. The findings underscore the urgency of digital literacy initiatives and ethical algorithmic reforms to mitigate these issues. These interventions are critical for fostering informed, inclusive, and constructive public discourse in the digital era. Keywords: